Răspuns :
A) 7x+5(x+3)-10=x+20→
7x+5x+15-10=x+20→
12x+5=x+20→
12x-x=20-5→
11x=15→
x=15 supra 11
B)ti-l scriu acum
a) 7x+5(x+3)-10=x+20 b)2(x+5)-x+3(x-1)=35 c)84:(x-3)=12
Desfiintam paranteza Desfiintam parantezele: Desfiintam paranteza
7x +5*x+5*3-10=x+20 2*x+2*5-x+3*x-3*1=35 84:x-84:3=12
7x+5x+15-10=x+20 2x+10-x+3x-3=35|-10 84:x-28=12|+12
12x+5=x+20 2x-x+3x-3=25
x+3x-3=25
4x-3=25|+3
4x=28|:4
x=7
Desfiintam paranteza Desfiintam parantezele: Desfiintam paranteza
7x +5*x+5*3-10=x+20 2*x+2*5-x+3*x-3*1=35 84:x-84:3=12
7x+5x+15-10=x+20 2x+10-x+3x-3=35|-10 84:x-28=12|+12
12x+5=x+20 2x-x+3x-3=25
x+3x-3=25
4x-3=25|+3
4x=28|:4
x=7